Lefebvrean analyses of the South Africa-Botswana international border and borderlands - Nkooe, Seanokeng Ernestina (Department of Environmental and Geographical Science, 2025)
International borders and borderlands are geographically organized political spaces which are primary objects of geographical research. This cluster of geographic border spaces embody the territorial dimensions of Lefebvre's scholarship which are critically under advanced and not readily appropriated in political geography. To address this gap, I advanced Lefebvre's spatiology and rhythmological science territorially for the critical analyses of South Africa's international border with Botswana, and its Batswana inhabited borderlands along the NorthWest Province, Southern District and South Eastern District respectively. Through a qualitative methodological design of spatial rhythmology underpinned by ethnographic as well as archival techniques, I made the following discoveries pertaining the political geography of Tswana populations straddling the international border of South Africa and Botswana at A1 and A2 border gates. I found that (a) the A1-A2 border-gated region of South Africa and Botswana is a territorial polyrhythmia in which the African society of Batswana are the dominant culture. (b) The A1 cross-border gates and borderlands of South Africa and Botswana are dominated by the Tshidi Barolong of Kgosi Montshiwa I, whose prehistoric dynasty is divided between the North-West Province and Botswana's Southern District, while the minority Batloung of Kgosi Shole are ensconced by the transnational Tshidi Barolong. (c) Political relations between the Barolong of Botswana and the Batloung of South Africa are eurhythmic however, the territorial specter of Apartheid and Bophuthatswana interstate histories threatens eurhythmic relations between South African Barolong and the Batloung of Greater Mahikeng, with arrhythmia. (d) There are no tangible cross-border governance structures and interstate relations between South Africa and Botswana despite a high degree of spatial integration and cross-border social interaction. (e) South Africa's international border with Botswana is an asymmetrical fracture line and monumental state space comprising superimposed spaces of accessibility, non-synchronized temporal rhythms, relatively fixed junction points and permanently established places of abode inhabited by a variety of Batswana. (f) The geopolitical spatial practices and asymmetric spatial rhythms of the international border of South Africa and Botswana produce binary border regimes which are directly influenced by interstate variations in their respective international border management practices and migration policies. These findings have significant implications for the Lefebvrean understandings of the contemporary political geography of the Batswana inhabited cross-border region of Southern Africa. Furthermore, the findings enhance the critical need for international border policymakers in the African sub-region to make empirically informed decisions pertaining interstate governance of territorial fracture lines, and the co-management of crossborderlands with territorial societies that inhabit them.